“Knowing One’s Self”: Selfwriting, Power and Ethical Practice - Valerie-Lee Chapman (Adult Education Research Conference, 2002)
Adult educators are increasingly concerned with issues of power and identity. Drawing on my research text, The Body’s Tale, and Foucault’s writings, I explore how pastoral power effects construct subjectivities. Using three genealogical narratives—of eating, elimination and swarming—I show how we can interrupt self-regulation, and through self-writing, develop an embodied ethical practice.